Czy pragmatyka jest u Kelsena możliwa? - Zalewska, Monika (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The main goal of Hans Kelsen’s Pure Theory of Law is to build a science of law. Kelsen is looking for a valid conditions of legal science and find them in neokantian philosophy. However, in the last phase when he turns into linguistic paradigm, he can’t explain science of law through neokantian terms anymore. In this case the question arises, how to recognize law from other linguistic expressions. Normally one could recall context of such expression (pragmatical context). In Kelsen’s case this is impossible as he distinguishes between is and ought and postulates that we should study law only on ought sphere. Despite this I will try to demonstrate that the pragmatics is possible in Pure Theory of Law by transforming previous neokantian categories into pragmatic ones.